2021
DOI: 10.48550/arxiv.2108.01963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deterministic Logarithmic Completeness in the Distributed Sleeping Model

Leonid Barenboim,
Tzalik Maimon

Abstract: In this paper we provide a deterministic scheme for solving any decidable problem in the distributed sleeping model. The sleeping model [8,22] is a generalization of the standard message-passing model, with an additional capability of network nodes to enter a sleeping state occasionally. As long as a vertex is in the awake state, it is similar to the standard message-passing setting. However, when a vertex is asleep it cannot receive or send messages in the network nor can it perform internal computations. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Its high-probability awake complexity is O(log n), and its worst-case awake complexity is polylogarithmic. Recently Barenboim and Maimon [6] showed a completeness on the class of decidable problems with a tight bound of Θ(log n) awake time complexity. That is, they offered an algorithm for solving any decidable problem in the sleeping model in O(log n) awake time but also showed a specific decidable problem which requires at least Ω(log n) awake time.…”
Section: Previous Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Its high-probability awake complexity is O(log n), and its worst-case awake complexity is polylogarithmic. Recently Barenboim and Maimon [6] showed a completeness on the class of decidable problems with a tight bound of Θ(log n) awake time complexity. That is, they offered an algorithm for solving any decidable problem in the sleeping model in O(log n) awake time but also showed a specific decidable problem which requires at least Ω(log n) awake time.…”
Section: Previous Workmentioning
confidence: 99%
“…In [6] the authors showed that given an acyclic orientation on the edge set of the input graph G, one can use the given orientation to build a binary tree internally in each vertex v and have v in the awake state exactly when one of its parents in the orientation sends information to v. This is facilitated to solve any O-LOCAL problem. In their paper, Barenboim and Maimon used a O(∆ 2 )-vertex-coloring to achieve this required acyclic orientation but we here capitalize on this idea and offer different ways to build an initial orientation such that, in terms of awake complexity, our algorithms are more efficient.…”
Section: Our Techniquementioning
confidence: 99%
See 3 more Smart Citations